Virtualization of the educational space as one of the intensification approaches of the educational process - Abeldina, Zh.K.; Moldoudarova, Zh.K.; Molmudarova, Zh.E.; Abeldina, R.K. (Recent Contributions to Physics, 2018)
One of the priority directions of the development of the world educational space is the digital revolution in teaching, which determines the use of digital technologies as tools for expanding and transforming the educational environment, so now we can talk about the phenomenon of virtualization of the educational environment. The relationship between the student and teacher is of great importance in training, especially to strengthen the motivation and deepen the cognitive process. The interaction reinforced by the virtual educational environment can be a powerful factor in improving the quality and effectiveness of training. The virtual instruments and software used at the same time are the most important interactive elements of the electronic educational process, especially when studying natural science disciplines. The target of research in the article is the dynamic interaction of participants in educational activities and the formed virtual educational space, which is a rapidly developing, multilevel and multifunctional system that combines methodological and pedagogical technologies, information resources and modern software. It was found that the virtual environment makes it possible to individualize learning not only by the pace of studying the material, but also by the logic and type of perception of students. Virtualization of the educational space gives students the opportunity to independently research the materials published in the Internet, offers assistance in finding answers to problematic issues.